Every Krapp counts: tracing an Object-Oriented Ontology in Krapp's Last Tape. Issue 11 (2nd November 2022) - Mansouri, Shahriyar
ABSTRACT: In an interview Samuel Beckett dismisses man as a 'non-knower' and a 'non-canner', a being that has lost its reign of cognitive agency. By so doing, Beckett not only defies the Heideggerian anthropocentric dictum of 'Man alone exists. Rocks are, but they do not exist', but also suggests a new reality wherein the subject is no longer the agent of meaning-making. Graham Harman's Object-Oriented Ontology introduces an uncanny way for the object to not just exist but to confirm the ways in which it independently performs the act of existence. This article reads Beckett's Krapp's Last Tape as the artist's prophetic caveat vis-à-vis the demise of anthropocentrism, inviting the audience to imagine an object-oriented reality. By drawing on OOO and Tool-Being, this essay examines the preexisting inter-reality of objects in Krapp's Last Tape known as 'the invisible realm' by tapping into their autonomous, and yet relation-oriented existence. The autonomy of the object that agitates the subject's cognitive balancewill be examined by exploring the interdependent struggle between the 'handiness of objects' known as zuhandenheit, and their 'ontic presence', vorhandenheit, and the ways in which an ontic reality of, for instance, a tape-recorder and a collection of tapes could reaffirm Krapp's ontological plasticity.